Diversity, Equity, and Inclusion: A Current Analysis of General Surgery Residency Programs. Issue 3 (March 2022) - Kearse, LaDonna E.; Jensen, Rachel M.; Schmiederer, Ingrid S.; Zeineddin, Ahmad; Anderson, Tiffany N.; Dent, Daniel L.; Payne, Davis H.; Korndorffer, James R.
Background: Local, regional, and national diversity, equity, and inclusion (DEI) initiatives have been established to combat barriers to entry and promote retention in surgery residency programs. Our study evaluates changes in diversity in general surgery residency programs. We hypothesize that diversity trends have remained stable nationally and regionally. Materials and Methods: General surgery residents in all postgraduate years were queried regarding their self-reported sex, race, and ethnicity following the 2020 ABSITE. Residents were then grouped into geographic regions. Data were analyzed utilizing descriptive statistics, Kruskal-Wallis test, and chi-square analyses. Results: A total of 9276 residents responded. Nationally, increases in female residents were noted from 38.0 to 46.0% ( P < .001) and in Hispanic or Latinx residents from 7.3 to 8.3% ( P = .031). Across geographic regions, a significant increase in female residents was noted in the Northwest (51.9 to 58.3%, P = .039), Midwest (36.9 to 43.3%, P = .006), and Southwest (35.8 to 47.5%, P = .027). A significant increase in black residents was only noted in the Northwest (0 to 15.8%, P = .031). The proportion of white residents decreased nationally by 8.9% and in the Mid-Atlantic, Southeast, and Southwest between 5.5 and 15.9% ( P < .05). Discussion: In an increasingly diverse society, expanding the numbers of underrepresented surgeons in training, and ultimately in practice, is a necessity. This study shows that there are region-specific increases in diversity, despite minimal change on a national level. This finding may suggest the need for region-specific DEI strategies and initiatives. Future studies will seek to evaluate individual programs with DEI plans and determine if there is a correlation to changing demographics.